2014
DOI: 10.4274/tod.08760
|View full text |Cite
|
Sign up to set email alerts
|

Romatoid Artrit Tedavisinde Akuaterapinin Etkinliği

Abstract: Objective: Rheumatoid Arthritis (RA) is a chronic destructive inflammatory disorder. This study is aimed to investigate the effects of balneotherapy and aquatherapy in the treatment of RA patients. Materials and Methods: A total of 59 patients who fulfilled the American College of Rheumatology diagnostic criteria for RA were included this study. Patients were randomly assigned into three groups. Group 1 (n=20) received balneotherapy, group 2 (n=20) received an aquatic exercise program and group 3 (n=19) was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Our study shows that high disease activity is not a contraindication for rehabilitation due to the fact that those patients get a significant increase in quality of life and life condition. The need and effectiveness of rehabilitation is confirmed in many studies based on the decreasing pain level and disease activity index [20][21][22][23][24][25][26]. In the study of Sukharev et al [27], DAS28 level decreased after rehabilitation in all groups regardless of the rehabilitation program.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Our study shows that high disease activity is not a contraindication for rehabilitation due to the fact that those patients get a significant increase in quality of life and life condition. The need and effectiveness of rehabilitation is confirmed in many studies based on the decreasing pain level and disease activity index [20][21][22][23][24][25][26]. In the study of Sukharev et al [27], DAS28 level decreased after rehabilitation in all groups regardless of the rehabilitation program.…”
Section: Discussionmentioning
confidence: 83%
“…Studies revealed that exercises focused on improving muscle strength in patients with rheumatoid arthritis had statistically significant impact on achieved results even after 24 weeks [ 31 ]. The review of the literature on the subject as well as the present research indicate that the progress in patient rehabilitation is not affected by factors such as disease activity according to the DAS28 indicator or the rehabilitation program [ 24 , 25 , 27 ]. Rehabilitation based on various forms of physiotherapy or training programs gives different results, while all of them prove effective [ 24 ].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation